LABORATORY DIAGNOSTICS OF CERVICAL CANCER - Aziza Anvarovna, Karimova; Chutbayevna, Kurbonova Zumrad; Ilhom Qizi, Nimatova Mohigul; Chutbayevna, Kurbanova Gavkhar (PT. Antis International Publisher, 2025)
Objective: This study examines current laboratory diagnostic techniques for cervical cancer, focusing on their application in diverse healthcare settings, with the goal of improving early detection and management. Methods: The research explores various diagnostic methods, including Pap smears, HPV DNA testing, and visual inspection with acetic acid (VIA), alongside advancements such as liquid-based cytology, molecular biomarkers, and artificial intelligence (AI). Comparative analysis highlights their effectiveness, sensitivity, and suitability across resource-diverse contexts. Results: Findings reveal that co-testing with cytology and HPV DNA testing offers superior sensitivity, while molecular diagnostics and liquid biopsy show promise for precision medicine. AI-based tools enhance diagnostic efficiency, particularly in underserved regions. However, challenges in accessibility, cost, and expertise persist in low-resource settings. Novelty: This study underscores the transformative potential of emerging technologies like AI-assisted diagnostics and liquid biopsy, emphasizing their role in bridging healthcare disparities and supporting the World Health Organization’s goal of eliminating cervical cancer by 2030.